Neurocognitive considerations when assessing Theory of Mind in Autism Spectrum Disorder. Issue 3 (31st October 2016) - Hamilton, Katie; Hoogenhout, Michelle; Malcolm-Smith, Susan
Abstract : Autism Spectrum Disorder (ASD) is characterised by poor social competence; and since Theory of Mind (ToM) is a building block for social-communicative skills and successful social integration, these skills are important to assess when preparing and monitoring educational and therapeutic plans. ToM is a complex skill requiring the ability to form mental concepts, to represent complex constructs verbally, to inhibit some mental states in favour of others, and to consider and compare multiple perspectives. It is critical to consider cognitive influences on the ability to develop and convey ToM skills to ensure that deficits in other cognitive domains do not falsely present as ToM deficits. This consideration is particularly vital in ASD populations with known difficulties not only in ToM, but also in intellectual functioning, language, and executive functioning. This article reviews the influence of intellectual ability, language, working memory, and inhibition skills on the presentation of ToM; with particular focus on ToM in ASD. We discuss practical suggestions based on clinical experience in neuropsychological practice and research in South Africa for the successful assessment of ToM ability.